2016
DOI: 10.1071/an15265
|View full text |Cite
|
Sign up to set email alerts
|

Animal nutrition in a 360-degree view and a framework for future R&D work: towards sustainable livestock production

Abstract: Abstract. As a result of a growing population, national economies and urbanisation the consumption of animal products has risen sharply and will also rise substantially in the future, leading to a huge demand for animal feed. This paper illustrates that feed impacts almost all sectors and services of the livestock sector and its sustainability hinges on how feed is produced and fed. A 360-degree view of animal nutrition is presented, illustrating linkages between animal nutrition and various other domains of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 42 publications
0
44
0
2
Order By: Relevance
“…Feed is an integral part of the food chain, and it plays an important role in the growth, welfare, and productivity of farm animal as well as in the composition, safety, and quality of livestock products (milk, meat, and eggs) in the food supply chain (Guerre 2016;Makkar 2016). A complete or finished feed is manufactured from a mixture of raw materials of plant, animal, industrial, and pharmaceutical origin, and formulated to achieve a range of objectives in animals regarding health and performance (Ittiphalin et al 2015;Guerre 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Feed is an integral part of the food chain, and it plays an important role in the growth, welfare, and productivity of farm animal as well as in the composition, safety, and quality of livestock products (milk, meat, and eggs) in the food supply chain (Guerre 2016;Makkar 2016). A complete or finished feed is manufactured from a mixture of raw materials of plant, animal, industrial, and pharmaceutical origin, and formulated to achieve a range of objectives in animals regarding health and performance (Ittiphalin et al 2015;Guerre 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable feed production and feeding are key factors in achieving resource-efficient and resilient livestock production systems with minimal environmental load and high product quality (Makkar, 2016). A sustainable animal diet is characterized as a diet that is balanced in all nutrients and free from harmful components, meets production objectives, generates animal products safe for human consumption, and integrates the planet, people, profit, and ethical dimensions of sustainability (Makkar and Ankers, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To maintain or raise the performance of current available livestock population and its productivity, we need to enhance the quality forage production and its productivity to achieve minimum optimum balanced feeding of livestock's. Feeding in dairy farming is the utmost important management factor because it is attributed to around 65-70% of the total input cost of animals (Makkar, 2016). Surve et al (2011) also reported that availability of green fodder with good quality is the key to success of dairy enterprises and without supply of quality fodder it is difficult to maintain the health and milk production level of the animals.…”
Section: Introductionmentioning
confidence: 99%